Long‐term outcome of antineutrophil cytoplasmic antibody‐associated small vessel vasculitis after renal transplantation. (20th February 2013) - Marco, Helena; Mirapeix, Eduard; Arcos, Emma; Comas, Jordi; Ara, Jordi; Gil‐Vernet, Salvador; Puig, Josep; Vinyas, Odette; Perello, Manel; Oppenheimer, Federico; Poveda, Rafael; Ibernón, Meritxell; et al.
Abstract The survival after renal transplantation of patients with antineutrophil cytoplasmic antibody (ANCA)‐associated to systemic vasculitis is as good as in other diseases, although most of the reports are based on small numbers of patients. Furthermore, it is not known whether comorbidities (cardiovascular [CV] disease and cancer) are more frequent than in general population. We report our experience and the analysis of the published data on this topic. The outcome after transplantation in 49 patients with ANCA‐associated small vessel vasculitis was compared with a control group. The relapse rate of vasculitis was 0.01 per patient per year. Comparison with the control patients revealed no difference in long‐term outcome, CV mortality or incidence of malignancies. In the published literature, patients with ANCA at transplantation and with Wegener's granulomatosis are at greater risk of relapse. Taking our own results together with the review of the literature, we conclude that patient and graft survival rates compare favorably with those in control group that the recurrence rate is very low and that there is no increase in the incidence of cancer or in CV mortality. Patients with ANCA at transplantation and with Wegener's granulomatosis have a higher relapse rate.